Effect of High Speed Rail Transit and Impact Loads on Ballast Degradation - Keeng, N.; Li, Jun; Hao, H. (SPRINGER-VERLAG BERLIN, 2015)
The emerging need of railway as a principal means of massive transport has encouraged the development of high speed trains in Australia. Large and frequent cyclic loading from heavy and fast trains leads to a progressive deterioration of the underlying railway structural system. The lack of research on degradation of ballast to counter the effects of high speed trains threatens the reliability and safety of train services and hence leads to more frequent and costly maintenance. Compaction testing with the Amsler equipment was conducted to deliver a graphical representation of fouling rates and the loading at which ballast becomes ineffective. The hammer drop test was employed to predict the service life of ballast under cyclic loading. Finite element analysis of a railway structural system subjected to a moving wheel with varying train speeds was conducted to obtain impact forces on sleeper and ballast under wheel flat effect. The deformation and stress behaviour of rail and ballast were investigated. It has been found that trains exceeding 210 km/h with a 100 mm wheel flat defect pose an immediate threat of accelerated fouling of ballast. Key findings also include the detection of different stages of ballast interaction, the observation of critical fouling force and the service life prediction of ballast under different train speeds.